ANALYZING THE IMPACT OF INDONESIAN SUSTAINABLE PALM OIL (ISPO) CERTIFICATION AND THE FACTORS THAT INFLUENCE CRUDE PALM OIL (CPO) EXPORTS VOLUME - Hajar, Rizqa Siti; Yun, Byung-Wook; Hwang, Hwa-Seok (Ridwan Institute, 2024)
This study examines the impact of Indonesian Sustainable Palm Oil (ISPO) certification on Indonesian Crude Palm Oil exports and other factors, such as commodity production and prices, exchange rates, and production levels. The data covers total CPO volume (HS codes 15111000 and 15119000) from January 2006 to December 2022, focusing on ISPO certification for large State-owned and Private Enterprises in palm oil cultivation and processing. The analysis employs the Difference-in-Differences (DID) method and multiple linear regression (MLR) to identify the linear relationship between the dependent and independent variables. The DID analysis revealed that Indonesian CPO production and global CPO prices significantly affected CPO export volumes, while soybean oil prices and effective exchange rates were not statistically significant in the regression model. The results provide valuable insights for policymakers and industry stakeholders in developing strategies that support sustainable growth, enhance competitiveness, and maintain Indonesia's leading position in the global palm oil market. Policymakers should focus on encouraging broader adoption of ISPO among palm oil producers through incentives, training, and technical support, especially for smaller producers.